SOME CHEMICAL TRANSFORMATIONS OF 2-CARBOXYETHYL-4-SUBSTITUTED-4-PENTANOLIDS (Proceedings of the YSU B: Chemical and Biological Sciences, 2011)
New derivatives of lactone-contaning thioureas and amides of carboxy-lactones have been synthesized on the base of carboxylactones.
Keywords: derivatives; lactone-contaning thioureas; carboxy-lactones